The Contribution Nonformal Education in Tourism Development Through Empowerment and Training of Street Vendors - Ariefianto, Lutfi; Hilmi, Muhammad Irfan (Universitas Negeri Semarang, 2019)
Jember Regency has a Malikan White Sand Beach tourist attraction known as